The Role of Handep Hapakat in Marriage among the Dayak Ngaju Community of Petuk Katimpun: An Islamic Legal Perspective - Nasharuddin, Muhammad Rif’an; Elmi, Ibnu; Helim, Abdul (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2025)
This research examines the local tradition of Handep Hapakat in the marriage practices of the Ngaju Dayak community in Petuk Katimpun Village, Central Kalimantan, and analyzes its compatibility with Islamic law. The Handep Hapakat tradition is a tradition that has been carried out for generations and is not only practiced at weddings but also in other activities. Handep Hapakat is carried out by traditional deliberations between the families of the bride and groom to reach consensus on various aspects of marriage which contain values of understanding, social harmony, and collective responsibility. The practices carried out in the concept of handep hafakat are in line with Islamic principles such as shura and social justice. This research is a leatherative research that aims to understand the phenomenon in depth through the collection of non-numerical data so that an understanding of the event can be explored. The approach in this research is normative-anthropological, this article provides contextual legal interpretation through the perspective of fiqh and cultural anthropology. The values of deliberation, mutual cooperation, mutual respect, and social responsibility contained in Handep Hapakat reflect the philosophy of life of the Ngaju Dayak people who uphold togetherness. The Handep Hapakat tradition carried out by the Ngaju Dayak community actually has an essential affinity with the concept of shura (deliberation) in Islam. This tradition can serve as a complement or even a reinforcement in building a marriage structure that is not only legal in Islamic law, but also socially and culturally strong. The findings show that Handep Hapakat can be categorized as 'Urf Shahih as long as it does not contradict the main provisions of Islamic marriage law, such as the presence of a guardian, witnesses, and dowry. This article contributes to the discourse of legal pluralism in Indonesia and encourages cooperation between traditional and religious leaders to harmonize local traditions with Sharia. An open issue that needs to be followed up is the regulation of the excessive burden of customary obligations on the male party.